Aspects of multilingualism - Mekt, Gebreiyesus (Yayasan Mitra Persada Nusantara, 2023)
In this paper the researcher needs to discuss fundamental issues related to multilingualism. The first is the concept of multilingualism and the different perspectives on it. Multilingualism can refer to either the use of language or the competence of an individual or to the language situation in an entire nation or society. The multilingualism describes the co- existence, contact and interaction of different languages. The co- existence can take place on a social or individual level. A society can have many different languages spoken and used by different group of peoples. The people themselves do not necessarily have to be multilingual. Likewise, individuals in a community can be multilingual while only recognizes one language for public use through legislation and other form of regulatory control. For society or an individual to become multilingual, contacts and interaction between languages are essential. The coexistence of different languages in society or an individual presupposes fundamental things that are different languages, these different languages have the possibility to come into contact to each other and human being is able to learn and use several languages and also human societies are able to adapt and manage multiple languages. In the next issue we will look at how the choice between languages can be given the same social and affective meaning as the choice of style in a language and the vitality of linguistic diversity in a multilingual community. The selection of the appropriate diversity in multilingual communities depends on social factors and dimensions and the repertoire of the addressee. The factors influencing a speaker's or writer's choice of language vary, and they include the context surrounding the speaker or writer, age, gender, culture, etc. Very often, the choice of language is deliberate and deliberate speaker can change the choice depending on such factors. In the context of an increasingly diverse world, it is important to continue to study multilingualism from all perspectives. It is crucial to continue to explore questions about how, when, and why speakers use certain languages and languages. The effects are not relevant from a stylistic point of view. They can show differences in the relative position of speakers within their societies, indicate power struggles and inequalities.